Existence of Licence, Infrastructure, and Energy Recources in Increasing Small Business Capacity in Sidoarjo District in The New Normal 4.0 - I Putu Artaya; Tubagus Purworusmiardi; I Gede Arimbawa; Made Kamisutara (LPPM of NAROTAMA UNIVERSITY, 2020)
This research was conducted in Sidoarjo Regency which has a lot of potential to grow and develop small businesses in three regions that is Krembung, Jabon, and Tulangan. The problem is one of the potential growth and development of small business activities in these three districts which has been supported by increased speed in business licensing, adequate infrastructure and the availability of renewable energy sources (gas) for smooth running and assistance for small businesses in the regions. To prove this, this research requires an increase in licensing, provision and improvement of infrastructure, and energy resources that can support its development activities for small business growth in the new normal 4.0. Of the three regions that were the object of research, at random there were 173 small business owners who were subjected to data collection in the field. As a basis for making decisions in an effort to overcome the above problems, the method used in this study is Crosstabs analysis, to test and determine whether there is a linearity between the potential for small business development with the availability of licensing management facilities, infrastructure provision, and supply of energy resources. the main pillar of the smooth running of small businesses in developing business activities, distribution and marketing of their products. From the test results, it turns out that the three facilities mentioned above, all have a linear relationship with the growth of small businesses in the three districts.